Dealing with low access to harm reduction: a qualitative study of the strategies and risk environments of people who use drugs in a small Swedish city - Julie Holeksa (BMC, 2022)
Abstract Background The development of harm reduction has been limited in many areas of Sweden. This study aims to understand the implications that this has for the life circumstances and risk management of people who use drugs in areas of low access. Methods Eleven qualitative, semi-structured interviews were undertaken with people who use drugs in a small urban centre with no needle and syringe exchange program (NSP) or Housing First policy. Results Participants reported many solutions to lack of NSP, including travel to an external NSP, creating bridging distribution networks, stealing, borrowing, reusing, ordering online, and smuggling injection equipment. They were at risk of having their equipment confiscated by police. Participants were mostly homeless, and to address exclusion from housing services, were forced to frequently find new temporary solutions, sheltering themselves in public places, with friends, in cars, among others. Participants felt the lack of services reflected stigmatized notions of drug use and heightened their exclusion from general society. For example, they avoided accessing other health care services for fear of discrimination. These issues caused high levels of stress and anxiety, in addition to serious risk for many somatic and psychological health conditions, including HIV and HCV transmission. Conclusion Lack of harm reduction services placed a great burden on study participants to develop strategies due to gaps in official programming. It also contributes to a vicious cycle of exclusion from services. The implementation of such evidence-based programs will reduce this burden, as well as provide the indirect, symbolic effect of inclusion.